Pengaruh Labelisasi Halal, Citra Merek, Online Customer Review, Selebrity Endorsement Dan Perceived Advertising Value Terhadap Keputusan Pembelian Produk Kosmetik Yang Bersertifikat Halal - Siti Khofifah; Agus Supriyanto (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2022)
Consuming halal food is obligatory for every Muslim. Not only food and drinks are required but also cosmetics. Every country, especially one with a Muslim population, is expected to ensure that the goods to be used are halal-certified. The purpose of implementing a halal certificate is to provide clarity on its halal status, which can then convince consumers to buy it. The purpose of this study is to examine and analyze the effect of halal labeling, brand image, online customer reviews, celebrity endorsements and perceived advertising value on the decision to purchase halal-certified cosmetic products. This research was conducted on generation Z in Rembang Regency who had bought or used halal-certified cosmetic products. This research uses a quantitative approach with a correlation research approach, where correlation research is used to measure whether one or more variables have a relationship. The sample of this research was selected as many as 100 people using purposive sampling method through a questionnaire using the SPSS application. The data analysis techniques used are: descriptive analysis, instrument testing, traditional assumption testing, and hypothesis testing. The findings show that the purchase of halal-certified cosmetic products is significantly influenced by halal labeling, brand image, online customer evaluation, celebrity endorser, and perceived advertising value.